2007
DOI: 10.1002/bit.21534
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐catalyzed synthesis of fatty acid sugar ester using extremely supersaturated sugar solution in ionic liquids

Abstract: The low solubility of sugars has hampered the lipase-catalyzed synthesis of fatty acid sugar esters in organic solvents and ionic liquids (ILs), because several solvents that are able to effectively dissolve sugars are detrimental to enzymes. In this work, in order to prepare a high concentration of sugars in ILs, we have developed a new procedure that entails mixing an aqueous sugar solution into ILs followed by removal of the water from the solution. The glucose concentrations in the supersaturated [Emim][Tf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 26 publications
4
52
0
Order By: Relevance
“…To overcome these problems, a new procedure 'water-mediated supersaturation' was recently used to prepare highly concentrated sugars in ILs [13]. Two separate graphs in Fig.…”
Section: Supersaturated Glucose Solution In Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these problems, a new procedure 'water-mediated supersaturation' was recently used to prepare highly concentrated sugars in ILs [13]. Two separate graphs in Fig.…”
Section: Supersaturated Glucose Solution In Ilsmentioning
confidence: 99%
“…Recently, we developed a new procedure to prepare supersaturated sugar solution in ILs through water-mediated method resulting in significantly enhanced synthetic yield and initial rate in the enzymatic transesterification of glucose with vinyl laurate [13]. Based on this method, therefore, the effect of pure ILs and their mixture, substrate ratio, water content, lipase content, and temperature on the activity and stability of lipase was studied in present work to pursue a further investigation on the optimization of reaction conditions for the lipase-catalyzed direct esterification of sugar with free fatty acid in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported in the literature but for different types of ILs. For example, Lee et al [18] found that the solubility of fructose in ethylmethylimidazolium tetrafluoroborate, ethylmethylimidazolium trifluorosulfonate, butylmethylimidazolium tetrafluoroborate and butylmethylimidazolium trifluorosulfonate, at 25 º C is 7.7, 32.8, 3.3, and 27 g/L, respectively, while the solubility of glucose under the same conditions was 1.1, 6.1, 0.9, and 4.8 g/L, respectively. It is clear that the effect of the anion on the extent of solubility is stronger than that of the cation.…”
Section: Resultsmentioning
confidence: 99%
“…Candida antarctica lipase B was the best enzyme for synthesis of glucose esters in a two-phase system containing an ionic liquid and tert-butanol [31]. Recently, the use of supersaturated sugar solutions [32] and ultrasonic treatment [33] has been reported to make sugar ester synthesis in ionic liquids even more efficient.…”
Section: How To Make Lipase-catalysed Carbohydrate Ester Synthesis Efmentioning
confidence: 99%